Menantang Negara Sekuler: Upaya Islamisasi Hukum di Indonesia - Muhammad Adlin Sila (Studia Islamika, 2009)
Book Review: Arskal Salim, Challenging the Secular State: The Islamization of Law in Modern Indonesia. (Honolulu: University of Hawaii Press,2008), xiv + 256.The book by Arskal Salim is one of the scholarly works which examines the relation between religion [Islam] and state, in particular the dynamics of its relation in contemporary Indonesia. The main focus of the discussion concerns with islamization of law in modern Indonesia, which consists of three points: constitutionalization, nationalization, and localization. The first two points refer to how shari'ah (Islamic law) is integrated into state constitution and implemented in act. The last part refers to the way the sharti'ah (Islamic law) is made as the foundation of issuing regional regulation (peraturan daerah) or qanun in Aceh, which regulate citizens' right and obligation in regional level.DOI: 10.15408/sdi.v16i2.486